Biometry, length-weight and length-length relationships of flathead sillago Sillaginopsis panijus (Hamilton, 1822) (Perciformes: Sillaginidae) from the north-western Bay of Bengal - Pradhan, Suraj Kumar; Roul, Subal Kumar; Ghosh, Shubhadeep; Tripathy, Pritam; Jaiswar, A. K.; Bhusan, Sashi; Nayak, B. B. (Indian Journal of Fisheries, 2020)
Biometry, length-weight relationships (LWRs) and length-length relationships (LLRs) of Sillaginopsis panijus (Hamilton, 1822) were investigated in the Indian coast of north-western Bay of Bengal. Altogether 622 specimens were collected between August 2018 and September 2019 from landings by trawls (30-35 mm mesh size), gillnets (15-55 mm mesh size) and shore seines (7-15 mm bag mesh size). The total length and weight of the specimens ranged from 7.8-40.3 cm and 2.9-506 g, respectively. The LWR established was W=0.0048 L3.059 for males, W=0.0032 L3.185 for females and W=0.0047 L3.0645 for indeterminates, indicating positive allometric growth pattern. All the LWRs were highly significant (p